A new expression for inertial particle collection efficiency by nanofibers with slip effect. (14th December 2022) - Yang, Hui; Fu, Haiming; Zhu, Hui
Graphical abstract: Highlights: Accurate flow field calculations for nanofibers in slip/transitional flow regime. The impacts of Knudson number, fiber packing density, interception parameter and Stokes number on inertial particle filtration performance are investigated. An increase in particle collection efficiency with Knudsen number is demonstrated, especially for particles with small size and weak-inertia. Slip effect has a negligible influence on particle deposition distribution on the nanofiber surface. A new prediction expression for particle collection efficiency of nanofibers due to the combination effects of inertial impaction and interception is developed. Abstract: The inertial particle filtration process of nanofibers in slip/transitional flow regime is studied by numerical methods. Effects of fiber Knudson number (Knf ), fiber packing density ( C ), interception parameter ( R ), and particle Stokes number (St) on particle filtration performance are investigated. Results indicate that particle trajectories for slip flow are much closer to the fiber surface when compared to those with non-slip flow condition, which leads to a higher particle collection efficiency under slip flow condition than the case of no-slip flow. Particle collection efficiency improves as slip effect increases, especially for small and weak inertial particles, whereas, it is weakly related to slip effect for particles with large size and high-inertia. Particle deposition distribution on fiber surface is found to be negligibly influenced by slip effect. Based on the simulation results, a reliable prediction expression for particle collection efficiency of nanofibers due to the combination effects of inertial impaction and interception is developed in the range of 0.05 ≤ Knf  ≤ 2, 0.01 ≤  C  ≤ 0.1, 0.01 ≤  R  ≤ 0.5, 0.1 ≤ St ≤ 10.